International Scientific Siberian Transport Forum TransSiberia - 2021 Volume 2 - Manakov, Aleksey; Edigarian, Arkadii; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book presents innovations in the field of high-speed rail technology, hyperloop transportation technologies and Maglev system, information and communication technology (ICT) for intelligent transportation systems (ITS), multimodal transportation, sustainable freight transportation, and others. The papers presented in the book are proceedings of the annual scientific forum (3z(BTransSiberia(3y(B, which is the foremost Russian transport event that focuses on innovations in rail transport. The book also presents research in the field of railway engineering, health monitoring, inspection, NDT&E, and signal processing. Developments in the field of decarbonization of railway transport and new types of fuel as an alternative to electrification are proposed. The issues of sustainable operation and maintenance of railway systems and sustainable freight transportation, such as digitalization and AI technologies for sustainable asset management, operation, and maintenance of railway systems, have received a lot of research attention. The book serves as a medium for railroad academia and industry to exchange new ideas and share the latest achievements, as well as to continue supporting the productivity of the transport industry in a sustainable manner.s
Keywords: Transportation engineering; Traffic engineering; Electric power production; Transportation Technology and Traffic Engineering; Electrical Power Engineering; Transportation -- Congresses